2019
DOI: 10.1111/hex.12909
|View full text |Cite
|
Sign up to set email alerts
|

Engaging patients in primary care design: An evaluation of a novel approach to codesigning care

Abstract: Objective Recognition is growing that to create truly patient‐centred care, health‐care organizations need to partner with patients around care design. More research into the benefits of engaging patients and the most effective ways of partnering with them is needed. Methods This study assessed the process and impact of a collaborative effort to design a new clinic service that balanced the number of patient and clinical provider/staff codesigners involved and recruited patients to represent diverse perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Other strategies that helped to optimize engagement included having patient partner input as a standing agenda item for all meetings, and allowing ample time for patient partners to ask questions during meetings to ensure that patient partners did not feel rushed or inhibited in any way. Holding face-to-face meetings, building-in time in the agenda for researchers and partners to socialize, and avoiding the use of jargon, acronyms and clinical or academic language were also important, 42 , 43 …”
Section: Lessons Learnedmentioning
confidence: 99%
See 1 more Smart Citation
“…Other strategies that helped to optimize engagement included having patient partner input as a standing agenda item for all meetings, and allowing ample time for patient partners to ask questions during meetings to ensure that patient partners did not feel rushed or inhibited in any way. Holding face-to-face meetings, building-in time in the agenda for researchers and partners to socialize, and avoiding the use of jargon, acronyms and clinical or academic language were also important, 42 , 43 …”
Section: Lessons Learnedmentioning
confidence: 99%
“…This is consistent with other studies that stress the importance of matching patient experience, skills and background to the specific needs of the research to ensure that patient contributions are valued. 43 …”
Section: Lessons Learnedmentioning
confidence: 99%
“…For example, papers reported that the desire of both patients and staff to improve services was essential to success 24 51 52 and was often personally rewarding. [53][54][55] This motivation led to a sustained commitment to QI partnerships 9 51 53 and increasingly sophisticated levels of engagement. 53 The importance of patients and staff being Self-aware and reflective was also discussed.…”
Section: Personal Attributes Domainmentioning
confidence: 99%
“…Patient involvement in the development of care pathways is increasing 3,5 . Patients have been acknowledged for their unique experiences that can contribute to research‐based quality improvement 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Patient involvement in the development of care pathways is increasing. 3,5 Patients have been acknowledged for their unique experiences that can contribute to research-based quality improvement. 6,7 Funding bodies require patient and public involvement (PPI) such as Control in Australia.…”
Section: Introductionmentioning
confidence: 99%